Distribution and mixture of Cape and Cunene horse mackerel, Tachurus capensis and Tracherus trecae in the Angola-Benguela front in relation to environmental and other factors - Duarte, Agostinho Domingos Caholo (Department of Biological Sciences, 2014)
Bibliography: leaves 128-133.